(untitled) (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Agussalim, Umami N, Nurliyani, Agus A. 2021. The physicochemical composition of honey from Indonesian stingless bee (Tetragonula laeviceps). Biodiversitas 22: 3257-3263. The demand of honey has recently increased significantly, but this situation is widely used by irresponsible humans who made a fake honey. This present study aims to evaluate the quality based on the physicochemical composition of honey from Indonesian stingless bee Tetragonula laeviceps. Honey was obtained from three geographical origins in Indonesia, i.e. Sleman, Gunungkidul, and Lombok. The physicochemical composition of honey was analyzed such as moisture, ash, protein, pH, glucose/moisture ratio, and electrical conductivity, and amino acids. The results showed that the geographical origins had a highly significant effect (P<0.01) on moisture, pH, and significant effect (P<0.05) on ash, electrical conductivity, protein, and glucose/moisture ratio. Honey from Indonesian stingless bee T. laeviceps was found 17 amino acids were arginine, histidine, lysine, phenylalanine, isoleucine, leucine, methionine, valine, threonine, tyrosine, proline, glutamic acid, aspartic acid, serine, alanine, glycine, and cysteine. The dominant amino acids of honey from Sleman were glutamic acid, histidine, lysine, and arginine. Honey from Lombok were glutamic acid, aspartic acid, lysine, and histidine. Furthermore, honey from Gunungkidul were lysine, arginine, histidine, and phenylalanine. Honey from Sleman and Lombok have the best quality than honey from Gunungkidul based on the chemical composition and amino acids profile.